Character Education Through Dhikr Tariqa Qadiriyya Naqhsabandiyya Al-Usmaniyya Indonesia - Ma`arif, Muhammad Anas; Zuana, Muhammad Mujtaba Mitra; Munjiat, Siti Maryam; Kartiko, Ari; Rusydi, Ibnu; Rosyad, Ali Miftakhu; Maknuun, Lu’lu’il; Khambali; Supardi; Juhji (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the process of character building through the dhikr of the tariqa Qadiriyya Naqsabandiya Al-Usmaniyya located at the Al-Fitrah Islamic boarding school in Surabaya. This study used qualitative research with a phenomenological approach, knowing and analyzing the behavior of Al-Usmaniyya TQN followers through behavioral motives to form the perceived impact due to dhikr. The results of this study found from the identification of phenomenology related to the dhikr's behavior motives and character building as follows 1) self-control, 2) respecting differences, 3) humility, 4) love helping, 5) love peace. While the formation of character through dhikr could be obtained through 1) inculcation 2) habituation of dhikr and, 3) modeling (uswah hasanah).